The association between dietary polyphenol intake and attention-deficit hyperactivity disorder: a case-control study - Melika Darzi; Khadijeh Abbasi; Reza Ghiasvand; Mohsen Akhavan Tabib; Mohammad Hossein Rouhani (BMC, 2022)
Abstract Background Previous research found that diets high in fruits and vegetables improved symptoms of attention deficit hyperactivity disorder (ADHD). Nevertheless, the relationship between dietary polyphenol intake and the risk of ADHD was not assessed. Objective The purpose of this study was to see if there was a relationship between dietary polyphenol intake and the risk of ADHD in children in preschool and elementary school. Methods A total of 400 children aged 4 to 12 years old participated in this case-control research (200 children with diagnosed ADHD and 200 healthy controls). The presence of ADHD was diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders-V criteria. To calculate dietary polyphenol intake, a 168-item food frequency questionnaire and the Phenol-Explorer database were used. Results A significant negative association was observed between one unit increase in dietary polyphenol intake and risk of ADHD (OR: 0.995, 95% CI = 0.994 to 0.996, P < 0.001) in the crude model. This finding was still significant even after adjusting for body mass index, energy intake, socioeconomic status, gender, and age (OR: 0.992, 95% CI = 0.989 to 0.995, P < 0.001). Conclusion We found that the increased dietary intake of polyphenols is associated with a lower risk of ADHD in preschool and school children. Prospective studies are needed to corroborate these observations.